Synthesis of Fine Micro-sized BaZrO3 Powders Based on a Decaoctahedron Shape by the Microwave-Assisted Hydrothermal Method - Moreira, Mario L.; Andres, Juan; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Amer Chemical Soc, 2009)
Micro-sized decaoctahedron BaZrO3 powders were synthesized by means of a hydrothermal microwave method at 140 degrees C for 40 min. The X-ray diffraction, Raman, UV-visible, and inductively coupled plasma atomic emission (ICP-AES) spectroscopy, as well as measurements of photoluminescence (PL) emission, were used for monitoring the formation of a perovskite phase with random polycrystalline distortion in the structure. Two emissions at 477 and 526 nm were accompanied by increase in the gap values, indicating the existence of different emission mechanisms. A theoretical model derived from previous first principle calculations allow us to discuss the origin of the photoluminescence emission in BaZrO3 powders which can be related to the local disorder in the network of both ZrO6 octahedral and dodecaht.dral (BaO12) hence forming the constituent polyhedron of BaZrO3 system. Initial observations of a novel morphology of the BaZrO3 perovskite crystal growth based on decaoctahedron shape is demonstrated and indirectly related to photoluminescence emissions.